Parametric Modeling CAD-CAM of the Ankle and Pathological Related Situations - Cofaru, Nicolae Florin; Huzu, Iulia (Applied Mechanics and Materials, 2014)
It is primary object of the present study to create a 3D model of the human ankle and an axis system that will show the position the tibia and the foot on a healthy subject. Regarding this scope of the study, the first step in obtaining the 3D model of the bones is scanning. The graphic modeling software used is Catia V5 R20. It is another object of the present study to create an axis system that will be very easy to maneuver and on which we can show different pathological situations, not only on a healthy subject, creating their assembly reference systems considering the mechanical and anatomical axes existing and creating prerequisites for the study of different possible pathological situations. For this scope, was used a triorthogonal axis system called skeleton that is defined as a system of axes Euler. This means that the angles can change the grid, in the desire to analyze different situations. In this study the focus is on the situation of varus equinus, in which the foot leg is not aligned with the tibia, as it is on a healthy subject. It was realized an important element: the incorporation of geometric and dimensional references. The last object in this study is to determine the status of CAE, in order to study the stress and the strain. Creating the CAD system is very important because it can be used to study the osteoarticular system, treatment strategies and related surgery.